To slip the bonds of Earth - Flower, Amanda (Kensington Publishing Corp., 2024)
December 1903: While Wilbur and Orville Wright's flying machine is quite literally taking off in Kitty Hawk, North Carolina with its historic fifty-seven second flight, their sister Katharine is back home in Dayton, Ohio, running the bicycle shop, teaching Latin, and looking after the family. A Latin teacher and suffragette, Katharine is fiercely independent, intellectual, and the only Wright sibling to finish college. But at twenty-nine, she's frustrated by the gender inequality in academia and is looking for a new challenge. She never suspects it will be sleuthing... Returning home to Dayton, Wilbur and Orville accept an invitation to a friend's party. Nervous about leaving their as-yet-unpatented flyer plans unattended, Wilbur decides to bring them to the festivities... where they are stolen right out from under his nose. As always, it's Katharine's job to problem solve--and in this case, crime-solve. As she sets out to uncover the thief among their circle of friends, Katharine soon gets more than she bargained for: She finds her number one suspect dead with a letter opener lodged in his chest. It seems the patent is the least of her brothers' worries. They have a far more earthbound concern--prison. Now Katharine will have to keep her feet on the ground and put all her skills to work to make sure Wilbur and Orville are free to fly another day. --